Design of a Redundant Manipulator for Playing Table Tennis towards Human-Like Stroke Patterns - Zhangguo Yu; Qiang Huang; Xuechao Chen; Wen Zhang; Junyao Gao (Advances in Mechanical Engineering, 2014)
This study investigates the design of a 7-DOF humanoid manipulator capable of playing table tennis with human-like stroke patterns. The manipulator system includes a redundant arm, real-time stereo vision system, and a distributed motion control system. First, the size, weight, workspace, and motion capability of the designed arm are similar to those of a human's arm. The forward and inverse kinematics, and the Jacobian matrix of the redundant manipulator are formulated. Next, a distributed motion control system is designed. The ball trajectory prediction method is proposed. Then, a human-inspired optimization method based on Jacobian pseudoinverse and the comfort of the arm posture for stroke pattern trajectory is proposed to achieve human-like stroke patterns and decrease the counterforce exerted on the manipulator. Finally, the validity of the proposed system and methods is demonstrated via human-like stroke pattern experiments.